Anti-migraine effect of Areca Catechu L. nut extract in bradykinin-induced plasma protein extravasation and vocalization in rats. (2nd August 2015) - Bhandare, Amol M.; Vyawahare, Neeraj S.; Kshirsagar, Ajay D.
Abstract: Ethnopharmacological relevance: Areca catechu Linn. (Arecaceae) nut is a popular folk remedy for the treatment of migraine in Kerala and Tamil Nadu states of India. Aim of the study: This study was designed to investigate the effect of hydroalcoholic extract of A. catechu L. nut (ANE) treatment on migraine pain in rat models to strengthen its use as an anti-migraine therapy. Materials and methods: Bradykinin (0.1 μmol/kg) injection in to left femoral vein of rat produced PPE which was measured with luminescence spectrometer. Vocalizations were produced in rats with 10 μg of bradykinin infusion into common carotid artery. Phonogram was recorded before, during and for 5 min after bradykinin injection and sumatriptan was used as a standard anti-migraine drug. In both models, the ANE was orally administered at doses of 250 and 500 mg/kg, 60 min before bradykinin infusion. Results: The PPE was reduced in both ANE treated groups of rats. The percent fluorescein was significantly increased in positive control group (97.00±1.7%; p <0.0001) compared to negative control (63.87±1.2%). With ANE treatments (250 and 500 mg/kg) PPE was significantly decreased to 88.88±1.4% ( p <0.01) and 83.55±0.1% ( p <0.0001) compared to positive control group, respectively. On the other hand in the model of vocalization, with 250 and 500 mg/kg ANE treatment, vocalization was significantly reduced to 33.33% and 16.66%, respectively, compared to saline treated rats. The reduction in vocalization is comparable to the reference drug sumatriptan. Conclusion: The findings provide the strong evidence for anti-migraine potential of ANE in rat models of migraine. In summary, therapeutic intervention with ANE treatment could be a promising strategy for prevention of migraine. Graphical abstract: